2014
DOI: 10.1016/j.molcel.2014.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Structural Biochemistry of a Vibrio cholerae Dinucleotide Cyclase Reveals Cyclase Activity Regulation by Folates

Abstract: Cyclic dinucleotides are a newly expanded class of second messengers that contribute to the regulation of multiple different pathways in bacterial, eukaryotic, and archaeal cells. The recently identified Vibrio cholerae dinucleotide cyclase (DncV, the gene product of VC0179) can generate three different cyclic dinucleotides and preferentially synthesize a hybrid cyclic-GMP-AMP. Here, we report the crystal structural and functional studies of DncV. We unexpectedly observed a 5-methyltetrahydrofolate diglutamate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 27 publications
1
67
0
Order By: Relevance
“…Vibrio cholerae DncV is a close structural homolog of human cGAS (Kato et al, 2015; Kranzusch et al, 2014; Zhu et al, 2014), and the enzyme active sites of DncV and cGAS are similar enough that a single amino acid substitution converts human cGAS into a DncV-like 3′,3′ cGAMP synthase (Kranzusch et al, 2014). Given that the nv-cGAS sequence is predicted to have similar changes to catalytic pocket amino acids important for substrate positioning (Figure S2), we hypothesized that the 3′,3′ CDN nv-cGAS product is most likely to be 3′,3′ cGAMP.…”
Section: Resultsmentioning
confidence: 99%
“…Vibrio cholerae DncV is a close structural homolog of human cGAS (Kato et al, 2015; Kranzusch et al, 2014; Zhu et al, 2014), and the enzyme active sites of DncV and cGAS are similar enough that a single amino acid substitution converts human cGAS into a DncV-like 3′,3′ cGAMP synthase (Kranzusch et al, 2014). Given that the nv-cGAS sequence is predicted to have similar changes to catalytic pocket amino acids important for substrate positioning (Figure S2), we hypothesized that the 3′,3′ CDN nv-cGAS product is most likely to be 3′,3′ cGAMP.…”
Section: Resultsmentioning
confidence: 99%
“…Reverse engineering of the human cGAS’ active site based on that of DncV produced cGAS variants that synthesized exclusively 3′,3′-cGAMP 32 . Furthermore, a recent study also identified folate as an unexpected regulator of DncV 33 . Although the exact purpose of regulation by folate is not well understood, it is intriguing to note that folate binds to DncV in a similar pocket as double-stranded DNA does to cGAS 33 .…”
Section: Cyclic Dinucleotide (Cdn) Synthesis and Degradationmentioning
confidence: 93%
“…Furthermore, a recent study also identified folate as an unexpected regulator of DncV 33 . Although the exact purpose of regulation by folate is not well understood, it is intriguing to note that folate binds to DncV in a similar pocket as double-stranded DNA does to cGAS 33 . Together, these observations paint an evolutionary picture in which metazoan cells could have adopted a bacterial cyclase to create, with relatively modest changes, a cytosolic DNA sensor as defence against intracellular pathogens.…”
Section: Cyclic Dinucleotide (Cdn) Synthesis and Degradationmentioning
confidence: 93%
“…In contrast, 'Type II' CD-NTases like Vibrio DncV and many bacterial CD-NTases are catalytically active in the absence of ligand and constitutively synthesize nucleotide signals in vitro [16 ,17 ,18 ,19 ]. Vibrio DncV is inhibited upon binding to folate-like compounds including 5-methyltetrahydrofolic acid [18 ], a metabolite required for nucleotide biosynthesis, suggesting that regulation of Type II enzymes can occur through ligand binding events that repress enzyme function ( Figure 1b). Bacterial CD-NTase operons are frequently encoded within defense islands and have been hypothesized to be involved in phage resistance [19 ,20 ].…”
Section: Type I Cd-n Tase Signalingmentioning
confidence: 99%